MARKETING STRATEGY THROUGH COVID-19 PREVENTION MESSAGES IN GOJEK ADVERTISING “J3K” - Nur Hanifah, Debby; Suarli, Dimas; Cahya Indrawan, Yuvelia (UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
Advertising is a fundamental part of one of the functions of marketing strategy with the aim of not only informing the public but also aimed at influencing someone about the image of a product. The Covid-19 prevention content that is being discussed is an opportunity for the Gojek company to do marketing. Through YouTube media, the Gojek company aired the ad